Analysis of Load Balancing in Low-Voltage Distribution Substations - Asrul Anwar (PT Pustaka Intelektual Sutajaya, 2025)
This study investigates the impact of load imbalance in low-voltage distribution systems on energy efficiency and operational reliability, focusing on the PHMB substation managed by PT PLN ULP Cirebon Kota. Through a field-based quantitative case study, the research identifies a significant phase current imbalance—exceeding 20%—resulting in a high neutral current (90 A) and monthly energy losses of 358.20 kWh. A load redistribution strategy, shifting 13 A from Phase R and 43 A from Phase T to Phase S, successfully reduced the imbalance to 11.27% and lowered neutral current to 64 A. This intervention achieved a 49.5% reduction in monthly energy losses (saving 177.12 kWh) and halved power losses in the neutral conductor. The study highlights the practical benefits of structured load balancing in improving power quality and energy efficiency in Indonesian distribution networks. Findings contribute empirical evidence for utility-level decision-making and policy design in developing countries, especially where advanced automation is not yet widely implemented.